Cerveja artesanal witbier com adição de polpa de acerola (Malpighia emarginata): caracterização e análise sensorial - SOUSA, Cecila Leal de (Universidade Federal do Oeste do Pará, 2024)
This work aimed to produce and evaluate craft beers of the witbier type with levels of addition of acerola pulp (Malpighia emarginata DC). The production steps were: grain grinding; mashing; filtration and mash washing; boil and addition of hops and coriander; cooling; addition of acerola pulp; yeast inoculation and fermentation; carbonation; fill and maturation. The analysis carried out were soluble solids, pH, total acidity, dry matter and mineral matter, foam, color, determination of total phenolic compounds, antioxidant activity by the FRAP, ABTS and DPPH method, flavonoid content, and acceptability test. The experimental design was completely randomized, with four treatments and four replications. Where, T1- 0% (V/V), treatment without pulp addition (control treatment), T2- 5% (V/V) inclusion, T3- 10% (V/V) inclusion and T4- 20% (V/V) inclusion. Data analysis was performed using the SISVAR statistical software. The addition of acerola resulted in beers with higher acidity and lower pH, higher percentage of mineral matter and more stable foams. There were no significant differences for dry matter and flavonoid content between beers. The antioxidant capacity and concentration of phenolic compounds of beers increased linearly with the increase in acerola concentration. All the beers produced had good acceptability, but the T2 beer had a greater purchase intention by the evaluators. Thus, it was found that the acerola pulp used as an adjunct in the production of Witbier-type beers has potential to be explored by the brewing industry.